O exercício da cidadania segundo as teorias política e jurídica propostas por Ronald Dworkin - Inkis, Maria Beatriz D´almeida Ramos (2009)
This dissertation has the purpose of, in presenting the political and juridical theories of Ronald Dworkin, founded on the tripod of liberalism, equality and ethics, making these theories a direction to the effective exercise of citizenship, in a political, juridical and economical background affected by the globalization phenomenon. The work begins with the study of Dworkin s political theory, the cornerstones of which are liberalism not as a principle, but as an actual political structure; equality as a political virtue; and ethics as the source of two principles that base his theory: the principle of intrinsic value and the principle of personal responsibility. Then, it presents the study of the juridical theory of Dworkin, analyzing the importance of hermeneutics and the study of the several concepts of Law in the development of a new concept of Law. Finally, we reach the study of the citizenship, making an analysis of its conceptions, its relation with political rights, democracy and individual rights, as well as the influence of the globalization phenomenon in its concepts, principles and exercise, offering, as a paradigm and solution, Ronald Dworkin s political and juridical theories.